CONSUMERISM: FROM THE ETHICAL WORLDVIEW TO THE AESTHETICAL ONE - Черноног, Р. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article covers the research of axiological specificity of consumerism in context of the esthetic component enhancement within the scope of the modern perception of the world. Through the exposure of peculiarities of consumerism it is grounded that it penetrates into different spheres of social life and is being transformed into an independent life strategy.